The Role of Nursing in Managing Shortness of Breath Symptoms in COPD Patients: A Qualitative Literature Review - Seven Sitorus (Indonesian Journal Publisher, 2026)
This study aims to analyze in depth the role of nursing in managing dyspnea symptoms in patients with Chronic Obstructive Pulmonary Disease (COPD) through a qualitative-descriptive approach based on literature review. This study focuses on identifying effective nursing interventions, their implementation mechanisms, and their impact on dyspnea symptom control and improved quality of life for patients. Data were obtained from various scientific sources such as international journals, research reports, and recent academic articles (2019–2025) relevant to the research topic. Data analysis was conducted through the stages of theme identification, data reduction, concept categorization, and inductive conclusion drawing to obtain a comprehensive understanding of the phenomenon under study. The results showed that non-pharmacological nursing interventions such as pursed-lip breathing, diaphragmatic breathing, progressive relaxation, pulmonary rehabilitation, and self-education programs were proven to reduce the intensity of dyspnea, improve lung function, and increase patients' self-management abilities. In addition, the application of the empowerment-based care model and nurse-led pulmonary rehabilitation contributed to increased therapy compliance and psychological well-being of patients. Overall, these findings reinforce the strategic role of nurses as educators, facilitators, and companions in the comprehensive care of COPD patients and provide a theoretical basis for the development of evidence-based nursing interventions in the future.